Aerobic Microbial Community of Insectary Population of Phlebotomus papatasi. - Naseh Maleki-Ravasan; Mohammad Ali Oshaghi; Sara Hajikhani; Zahra Saeidi; Amir Ahmad Akhavan; Mohsen Gerami-Shoar; Mohammad Hasan Shirazi; Bagher Yakhchali; Yavar Rassi; Davoud Afshar (Tehran University of Medical Sciences, 2014)
Background: Microbes particularly bacteria presenting in the gut of haematophagous insects may have an important role in the epidemiology of human infectious disease. Methods: The microbial flora of gut and surrounding environmental of a laboratory strain of Phlebotomus papatasi, the main vector of Zoonotic Cutaneous Leishmaniasis (ZCL) in the old world, was investigated. Biochemical reac- tions and 16s rDNA sequencing of the isolated bacteria against 24 sugars and amino acids were used for bacteria species identification. Common mycological media used for fungi identification as well. Results: Most isolates belonged to the Enterobacteriaceae, a large, heterogeneous group of gram-negative rods whose natural habitat is the intestinal tract of humans and animals. Enterobacteriaceae groups included Edwardsiella, Enterobacter, Escherichia, Klebsiella, Kluyvera, Leminorella, Pantoea, Proteus, Providencia, Rahnella, Serratia, Shigella, Tatumella, and Yersinia and non Enterobacteriaceae groups included Bacillus, Staphylococcus and Pseu- domonas. The most prevalent isolates were Proteus mirabilis and P. vulgaris. These saprophytic and swarming mo- tile bacteria were isolated from all immature, pupae, and mature fed or unfed male or female sand flies as well as from larval and adult food sources. Five fungi species were also isolated from sand flies, their food sources and colo- nization materials where Candida sp. was common in all mentioned sources. Conclusion: Midgut microbiota are increasingly seen as an important factor for modulating vector competence in insect vectors so their possible effects of the mirobiota on the biology of P. papatasi and their roles in the sandfly- Leishmania interaction are discussed.